Synthesis of a novel bifunctional nanocomposite with tunable upconversion emission and magnetic properties. Issue 113 (2nd November 2015) - Cheng, Qian; Li, Yu; Liu, Shouxin; Sui, Jiehe; Cai, Wei
Abstract : A method of Co 2+ ions codoping for significantly enhancing upconversion emission intensity and simultaneous controlling sparamagnetic properties in β-NaYF4 :Yb/Er nanoparticles, with well maintaining their morphology and highly disperse. Abstract : Fluorescent and magnetic bifunctional NaYF4 :Yb/Er/Co nanoparticles were synthesized for the first time via a thermalysis method using oleic acid as capping ligand and octadecene as solvent. The effect of Co 2+ -codoped on the size evolution, crystal structure, UC emission and magnetic properties of NaYF4 :Yb/Er nanoparticles was investigated in detail. XRD, EDS and XPS measurements revealed that Co 2+ ions had been successfully incorporated into NaYF4 matrix and existed in the host lattice under the II valence state. The different concentration of Co ions codoping did not change the structure of hexagonal phase. However, the green and red upconversion (UC) emissions intensity of hexagonal NaYF4 :Yb/Er were obviously strengthened by tridoping the structure with Co 2+ /Yb 3+ /Er 3+, and the decay time was obviously prolonged with different quantity of Co 2+ ions tridoping. The luminescence enhancement should be attributed to the distortion of the local asymmetry around Er 3+ ions. A possible mechanism for the enhancement of upconversion emission was discussed. More importantly, owing to the cobalt ion doping, the NaYF4 nanoparticles also present paramagnetic properties at room temperature and superparamagnetic properties at low temperature. Therefore, it is expected that these nanocrystals can be used as promising dual-modal nanoprobes for optical bioimaging and magnetic resonance imaging (MRI), and may have potential applications in bioseparation.